Response in BRCA1 mutation carrier with metastatic pancreatic adenocarcinoma treated with FOLFIRINOX. Issue 4 (29th April 2022) - Campoverde, Leticia Estefania; Batalini, Felipe; Bulushi, Yarab; Bullock, Andrea
Abstract : A woman in her 50s previously treated for early-stage breast cancer, parotid mucoepidermoid carcinoma and Caroli's disease was diagnosed with stage IV pancreatic ductal adenocarcinoma (PDAC) metastatic to the liver and was found to harbour a BRCA1 germline mutation. She had palliative chemotherapy, initially with 5-fluorouracil, leucovorin, irinotecan and oxaliplatin, and then FOLFIRI and capecitabine, achieving a sustained near-complete response for at least 86 months. Chemotherapy was eventually discontinued when she was diagnosed with a tongue squamous cell carcinoma. Despite withholding systemic therapy, she has maintained a durable response. This is the first report in the English literature showing a sustained duration of response in a patient with PDAC and BRCA 1 germline mutation.